2014
DOI: 10.1038/bmt.2014.112
|View full text |Cite
|
Sign up to set email alerts
|

Plerixafor plus pegfilgrastim is a safe, effective mobilization regimen for poor or adequate mobilizers of hematopoietic stem and progenitor cells: a phase I clinical trial

Abstract: The safety, kinetics and efficacy of plerixafor+pegfilgrastim for hematopoietic stem and progenitor cell (HSPC) mobilization are poorly understood. We treated 12 study patients (SP; lymphoma n = 10 or myeloma n = 2) with pegfilgrastim (6 mg SC stat D1) and plerixafor (0.24 mg/kg SC nocte from D3). Six SP were 'predicted poor-mobilizers' and six were 'predicted adequate-mobilizers'. Peripheral blood (PB) CD34 + monitoring commenced on D3. Apheresis commenced on D4. Comparison was with 22 historical controls (HC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 28 publications
1
6
0
Order By: Relevance
“… 76 Combining plerixafor with pegfilgrastim or with mobilizing chemotherapy seems safe and effective in PMs, but these results require confirmative data. 77 The main disadvantage of plerixafor is its cost, requiring the development of algorithms for the use of plerixafor in autologous HSPC mobilization. 78 …”
Section: Pb Hspc Harvesting: Mobilization and Apheresis Techniquesmentioning
confidence: 99%
“… 76 Combining plerixafor with pegfilgrastim or with mobilizing chemotherapy seems safe and effective in PMs, but these results require confirmative data. 77 The main disadvantage of plerixafor is its cost, requiring the development of algorithms for the use of plerixafor in autologous HSPC mobilization. 78 …”
Section: Pb Hspc Harvesting: Mobilization and Apheresis Techniquesmentioning
confidence: 99%
“…The effect of G-CSF plus plerixafor on tumor cell contamination of peripheral blood and apheresis product has been investigated in several studies [6,7,27,28]. One study of 12 patients (10 patients with lymphoma and 2 patients with myeloma) treated with plerixafor + G-CSF for stem cell mobilization showed no detectable tumor cells were present in the peripheral blood or apheresis product [6]. This finding was supported by the findings from another study that showed the absence of tumor cell mobilization after treatment with G-CSF and plerixafor in myeloma patients known to be poor mobilizers [7].…”
Section: Discussionmentioning
confidence: 99%
“…Concerns have been raised that agents that mobilize cells using the CXCR-4/CXCL12 interaction may theoretically also mobilize tumor cells [5,6]. The likelihood of tumor cell mobilization in peripheral blood and apheresis product at the same time of CD34 + cell mobilization continues to be controversial [7].…”
Section: Introductionmentioning
confidence: 99%
“…Even though the effect on HIV was quite disappointing, its ability to block the hematopoietic stem cell homing mechanism was noteworthy. Today, plerixafor is administered as a safe and efficient stem cell mobilizer during autologous or allogeneic stem cell collection [ 65 ].…”
Section: Strategies To Overcome Viral Reboundmentioning
confidence: 99%